2012
DOI: 10.12991/201216398
|View full text |Cite
|
Sign up to set email alerts
|

An ethnobotanical study of the useful and edible plants of Izmit

Abstract: An ethnobotanical study was carried out in İzmit province (Northwest Turkey). During this study, 145 specimens were collected from the area. Informations about plants such as their usages and used parts were recorded. The stud y revealed that, 96 plant taxa belonging to 42 families had ethnobotanical usages in this area. Among these 96 plant taxa, 60 taxa (51 wild, 9 cultivated) were used as edibles and 64 taxa (51 wild, 13 cultivated) were used for different purposes. The results of our study show that even i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 4 publications
1
32
0
3
Order By: Relevance
“…Roots are prepared by decoction to treat malaria [28]. While leaves are used externally as an antipyretic and analgesic [22] and for the treatment of joint ailments [31], they are used internally for the treatment of diarrhea and colds [29][30][31]. Rhizomes are also used for the treatment of diarrhea and colds, but the preparation and administration methods were not mentioned in the literature [30].…”
Section: Pharmacological Studies 321 Helleborus Orientalis Lam (Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Roots are prepared by decoction to treat malaria [28]. While leaves are used externally as an antipyretic and analgesic [22] and for the treatment of joint ailments [31], they are used internally for the treatment of diarrhea and colds [29][30][31]. Rhizomes are also used for the treatment of diarrhea and colds, but the preparation and administration methods were not mentioned in the literature [30].…”
Section: Pharmacological Studies 321 Helleborus Orientalis Lam (Rmentioning
confidence: 99%
“…Rhizomes are also used for the treatment of diarrhea and colds, but the preparation and administration methods were not mentioned in the literature [30]. According to other records, rhizomes are inserted into a cow's ear to treat colds [29] and they are added to fodder to treat diarrhea [29]. Moreover, they are administered externally against sunstroke [23].…”
Section: Pharmacological Studies 321 Helleborus Orientalis Lam (Rmentioning
confidence: 99%
“…Despite its comparative rarity, Ruscus aculeatus has a long and diverse history of usage in Europe. It has indeed been used as a ‘butcher's broom’ to clean chopping blocks (Pedersen ), also to make garden besoms (Bean ; Kızılarslan & Özhatay ) and brooms for removing embers from bread ovens in southern Italy (Salerno, Guarrera & Caneva ). Extracts from the rhizome have been used in many dietary supplements (Mari et al .…”
Section: Conservationmentioning
confidence: 99%
“…Despite its comparative rarity, Ruscus aculeatus has a long and diverse history of usage in Europe. It has indeed been used as a 'butcher's broom' to clean chopping blocks (Pedersen 1994), also to make garden besoms (Bean 1980;Kızılarslan & € Ozhatay 2012) and brooms for removing embers from bread ovens in southern Italy (Salerno, Guarrera & Caneva 2005). Extracts from the rhizome have been used in many dietary supplements (Mari et al 2012;Di Novella et al 2013;Di Sanzo et al 2013;Gonz alez et al 2013), for treating warts, chilblains, piles and minor pains (Guarrera 2005;Chauhan, Ruby & Dwivedi 2012;Akyol & Altan 2013), and more recent medicinal uses described in VI (F).…”
Section: Conservationmentioning
confidence: 99%
“…[4][5][6] An ethnobotanical study on useful and edible plants reported that peeling stems of C. creticum can be eaten as raw vegetable or cooked. 7 C. creticum (Asteraceae) which is wild plant species in Trakya region of Turkey. In the literature there is no study on the biological activity of C. creticum plants.…”
Section: Introductionmentioning
confidence: 99%